2019
DOI: 10.1097/mpg.0000000000002394
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Breast Milk Influences on the Infant Gut Microbiome, Enteric Health and Growth Outcomes of Rhesus Monkeys

Abstract: Objectives: Gut bacteria play an essential role during infancy and are strongly influenced by the mode of birth and feeding. A primate model was used to investigate the benefits of exposure to the mother or conversely the negative impact of early nursery rearing on microbial colonization. Method: Rectal swabs were obtained from rhesus macaques born vaginally and mother-reared (MR, N = 35) or delivered primarily via cesarean-section and human-reared (HR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
5
8
2
Order By: Relevance
“…Infant microbial profiles were dominated by Firmicutes at all time points, accounting for 52.6% of the total reads, followed by Bacteroidetes (31.9%), Proteobacteria (7.2%), and Actinobacteria (5.8%) (Figure 2A). In accordance with previous primate studies, 52,53 the predominant genus isolated from swabs was Prevotella within Bacteroidetes, which shifted significantly over the first year of life (LME: P = .003; Figure 2B). It increased 11% from abundances at 2 weeks of infant age as infants transitioned to solid foods before stabilizing.…”
Section: The Community Structure Of the Rhesus Infant's Gut Microbiom...supporting
confidence: 91%
See 2 more Smart Citations
“…Infant microbial profiles were dominated by Firmicutes at all time points, accounting for 52.6% of the total reads, followed by Bacteroidetes (31.9%), Proteobacteria (7.2%), and Actinobacteria (5.8%) (Figure 2A). In accordance with previous primate studies, 52,53 the predominant genus isolated from swabs was Prevotella within Bacteroidetes, which shifted significantly over the first year of life (LME: P = .003; Figure 2B). It increased 11% from abundances at 2 weeks of infant age as infants transitioned to solid foods before stabilizing.…”
Section: The Community Structure Of the Rhesus Infant's Gut Microbiom...supporting
confidence: 91%
“…The progressive shifts in the bacterial taxa that occur in the infant monkey are generally consistent with the human literature 1,55 . However, we and a number of other research groups have shown previously that the microbial composition of the infant monkey gut can be strongly influenced by breast milk and is markedly different if fed formula by humans in a nursery setting 6,57,58 . The initial nursing phase is characterized by less microbial diversity due to the predominance of taxa within Actinobacteria and Proteobacteria.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, we do know from animal studies if the mode of delivery can impact host immunity directly [108]. The NHP model could be useful to address the impact of the mode of delivery on the development of the immune system in longitudinal studies taking into account the temporal dynamics of vaginal microbiota and other confounding factors [109].…”
Section: Mode Of Delivery: C-section Vs Vaginal Deliverymentioning
confidence: 99%
“…Breast-fed and formula-fed infants present a different relative abundance of some phyla of bacteria [ 34 ]. The microbiota of breast-fed babies is more heterogeneous than that of formula-fed babies and contains a higher taxonomic diversity [ 35 ]. Mammary microbiota derives from the entero-mammary pathway through which maternal gut commensal bacteria across the intestinal barrier to the lymph/blood circulation, reaching the mammary gland epithelium.…”
Section: The Gut Microbiotamentioning
confidence: 99%